Couple's labor supply, taxes, and the division of housework in a gender-neutral lab - Melanie Schröder; Norma Burow (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We use a lab-in-the-field experiment to investigate intra-couple labor supply decisions and the division of housework under individual and joint income taxation systems. In order to eliminate problems of endogenous intra-couple time use decisions, we exogenously varied not only the taxation system but also the intra-couple roles of primary and secondary earners. Using work effort as a proxy for labor supply, 62 established couples, both cohabiting and married (124 participants), performed real effort tasks under a piece rate payment system within a given time. Prior to this paid task, couples had to decide upon the allocation of an unpaid task serving as our proxy for housework. In our gender neutral lab, we find tax-effects only on men's labor supply but not on women's and no gender differences in the allocation of housework. Instead, the allocation of housework follows a purely economic rationale with the majority of secondary earners taking responsibility. This is even confirmed by a shift to a more egalitarian allocation when individual taxation is applied. However, one result replicates real world findings with married male participants providing more labor supply than cohabiting men and married women less than cohabiting women. This result hinges on the stability of specialization in married couples, which seems to overcome the gender neutral lab.
Keywords: H31; D13; C93; J16; 330; real effort experiment; labor supply; housework; income taxation; household decision making; gender